PATRON KLIEN ANTARA TAUKE DAN PETANI KELAPA SAWIT DI DESA RAWA MULIA KECAMATAN SIMPANG KANAN KABUPATEN ROKAN HILIR - Agus Agus; Resdati Resdati; Mardatillah Mardatillah; Siti Wahyu Vitamagistra; Muhammad Faizal Dzulqarnain (Peneliti.net, 2026)
The development of oil palm in Indonesia is supported by climatic conditions suitable for the survival of oil palm plants. The purpose of this study is to determine the patron-client relationship between the touts and oil palm farmers in Rawa Mulia Village in Simpang Kanan District and the factors that cause the patron-client relationship between the touts and oil palm farmers in Rawa Mulia Village in Simpang Kanan District. This research method uses a qualitative research method. This study was conducted with six (6) research subjects according to predetermined criteria. There are three strategies that are usually used by someone when in a threatening condition, including a relationship strategy, a strategy of tightening the belt, and an alternative subsistence strategy. Data collection was carried out through the stages of observation, interviews, and documentation in the study. The results of the study, the touts and oil palm farmers have a reciprocal relationship that requires each other and relationship factors such as debt, trust, and culture. Patron-client relationship between touts and oil palm farmers in Rawa Mulia Village, Simpang Kanan District, Rokan Hilir Regency This relationship demonstrates a mutually beneficial relationship. This closeness stems from farmers' limited capital, limited market access due to the village's relatively remote geographic location, and the dominance of the